2023
DOI: 10.3390/ijms241612824
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanisms Employed by the Parasite Myxobolus bejeranoi (Cnidaria: Myxozoa) from Invasion through Sporulation for Successful Proliferation in Its Fish Host

Keren Maor-Landaw,
Itamar Avidor,
Nadav Rostowsky
et al.

Abstract: Myxozoa is a unique group of obligate endoparasites in the phylum Cnidaria that can cause emerging diseases in wild and cultured fish populations. Recently, we identified a new myxozoan species, Myxobolus bejeranoi, which infects the gills of cultured tilapia while suppressing host immunity. To uncover the molecular mechanisms underlying this successful parasitic strategy, we conducted transcriptomics analysis of M. bejeranoi throughout the infection. Our results show that histones, which are essential for acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 125 publications
0
6
0
Order By: Relevance
“…The M. cerebralis histone was found connected to host proteins in the protein–protein interaction network. This protein is likely essential for accelerated cell division and myxozoan stage differentiation, as seen in a previous study of Myxobolus bejeranoi where differential expression of histones were found to be associated with parasitic invasion ( Maor-Landaw et al., 2023 ). Calmodulin was also involved in the gill protein-protein interaction network, and is likely a key virulence factor that contributes to parasite motility and invasion of myxozoan parasites, as reported for other parasites ( Long et al., 2017 ).…”
Section: Discussionmentioning
confidence: 57%
“…The M. cerebralis histone was found connected to host proteins in the protein–protein interaction network. This protein is likely essential for accelerated cell division and myxozoan stage differentiation, as seen in a previous study of Myxobolus bejeranoi where differential expression of histones were found to be associated with parasitic invasion ( Maor-Landaw et al., 2023 ). Calmodulin was also involved in the gill protein-protein interaction network, and is likely a key virulence factor that contributes to parasite motility and invasion of myxozoan parasites, as reported for other parasites ( Long et al., 2017 ).…”
Section: Discussionmentioning
confidence: 57%
“…Free hemoglobin, the product of hemolysis, can be induced by various pathogens [ 49 ], which was recently reported as a feeding behavior of the myxozoan Sphaerospora molnari [ 50 , 51 ]. Upon infection, M. bejeranoi deploys an array of activated proteases, including cathepsin D and cathepsin L [ 29 ], which may act to degrade hemoglobin, as in other parasites [ 32 , 52 ]. This aligns with our findings, indicating decrease in globin proteins and an increase in endocytosis, the process in which macrophages engulf their targets [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Myxozoan parasites exploit their host and migrate through its tissues using a battery of secreted proteolytic enzymes [ 29 , 32 , 52 , 53 , 54 , 55 ]. Thus, a vital component in the host immune arsenal is protease inhibitors [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations